Pengaruh Kualitas Jaringan, Kualitas Pelayanan, dan Harga Terhadap Kepuasan Pelanggan pada PT. Telkom Infrastruktur Indonesia Pematang Siantar - M. Erifiandi; Zalikha Zalikha; Murni Murni (Aceh Cooperative Care, 2026)
This study aims to analyze customer satisfaction factors, using a case study at PT Telkom Infrastruktur Indonesia Pematang Siantar. There are inherent assumptions regarding satisfaction, related to network quality, service quality, and price. An associative research approach was applied with empirical evidence using statistics through a path analysis model. Data were collected through questionnaires from a sample of 96 customers. The results revealed: (1) There is a causal relationship between network quality, service quality, and price, with a fairly strong categorization (average 55%), with direct and indirect influences on customer satisfaction. (2) The direct and indirect influence of network quality on customer satisfaction is 70.6%, service quality is 79.9%, and price is 39.8%. (3) Together, all three contribute a significant positive contribution of 78,4% to the variation in changes in customer satisfaction at PT Telkom Infrastruktur Indonesia Pematang Siantar.